Ventricular Ectopy as a Predictor of Heart Failure and Death - Dukes, Jonathan W; Dewland, Thomas A; Vittinghoff, Eric; Mandyam, Mala C; Heckbert, Susan R; Siscovick, David S; Stein, Phyllis K; Psaty, Bruce M; Sotoodehnia, Nona; Gottdiener, John S; Marcus, Gregory M (Journal of the American College of Cardiology, 2015)
Studies of patients presenting for catheter ablation suggest that premature ventricular contractions (PVCs) are a modifiable risk factor for congestive heart failure (CHF). The relationship among PVC frequency, incident CHF, and mortality in the general population remains unknown. The goal of this study was to determine whether PVC frequency ascertained using a 24-h Holter monitor is a predictor of a decrease in the left ventricular ejection fraction (LVEF), incident CHF, and death in a population-based cohort. We studied 1,139 Cardiovascular Health Study (CHS) participants who were randomly assigned to 24-h ambulatory electrocardiography (Holter) monitoring and who had a normal LVEF and no history of CHF. PVC frequency was quantified using Holter studies, and LVEF was measured from baseline and 5-year echocardiograms. Participants were followed for incident CHF and death. Those in the upper quartile versus the lowest quartile of PVC frequency had a multivariable-adjusted, 3-fold greater odds of a 5-year decrease in LVEF (odds ratio [OR]: 3.10; 95% confidence interval [CI]: 1.42 to 6.77; p = 0.005), a 48% increased risk of incident CHF (HR: 1.48; 95% CI: 1.08 to 2.04; p = 0.02), and a 31% increased risk of death (HR: 1.31; 95% CI: 1.06 to 1.63; p = 0.01) during a median follow-up of >13 years. Similar statistically significant results were observed for PVCs analyzed as a continuous variable. The specificity for the 15-year risk of CHF exceeded 90% when PVCs included at least 0.7% of ventricular beats. The population-level risk for incident CHF attributed to PVCs was 8.1% (95% CI: 1.2% to 14.9%). In a population-based sample, a higher frequency of PVCs was associated with a decrease in LVEF, an increase in incident CHF, and increased mortality. Because of the capacity to prevent PVCs through medical or ablation therapy, PVCs may represent a modifiable risk factor for CHF and death.